(3ZhGeV GdUMGMs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj, UdGM GdOjf , J (B764 (3g` s; (3ESeGYjd Hf MeGO GdLhgQj, CHh fUQ,J (B393 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi fYe aGJ EMUGDgG aEf cJGH GdUMGM ddLhgQi hdcf ajg CdaGX jJY(B>(3Q cTagG Ydi eKdi s
(3BNQgG (B:s
(3ef GdjGA GdeKfGI ef JMJ bhdg (B: (3jhSa HVe GdSjf haJMgG hcSQgG hQHeG geRhG GdhGh efg ChQOg ai CSa gfG Je cJGH ZhGeV GdUMGM ddLhgQi s
(3HGdeeGdc GdTQjaI GdESdGejIs
(3HChdgG Jedc eDQN SfI (B951 (3g`s
(3YfhGf GdcJGH ePgHs
(3fSNI cJHJ HQSe GdNRGfg GdYdGFjg UGMH OhGhjf GdEfTGA GdTQja s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GddZIs